1959
DOI: 10.4141/cjps59-024
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Sprinkler Irrigation on Flue-Cured Tobacco

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1960
1960
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Walker and Vickery (9) found that low soil moisture Produced low yields of tobacco with rdladvely high nicotine content. Parups and Nielsen (7) investigated influence of soil temperature on growth of tobacco, found that22.2"C. soil temperature was best for growth of tobacco varieties Hicks and Resistant Havani 211, and that at low soil temPerarures Plants resPonded to phosphorus.…”
Section: Introductionmentioning
confidence: 99%
“…Walker and Vickery (9) found that low soil moisture Produced low yields of tobacco with rdladvely high nicotine content. Parups and Nielsen (7) investigated influence of soil temperature on growth of tobacco, found that22.2"C. soil temperature was best for growth of tobacco varieties Hicks and Resistant Havani 211, and that at low soil temPerarures Plants resPonded to phosphorus.…”
Section: Introductionmentioning
confidence: 99%